Discovering science child craft. - World Book, Inc. ([Chicago : World Book, 1987)
Illustrated articles, stories, and poems, grouped thematically in fifteen volumes under titles including "World and Space," "About Animals," "How Things Work," and "Make and Do."
"Portions of the text and certain illustrations previously published under the title of Childcraft--the how and why library"--T.p. verso.
0
Keywords: Children's encyclopedias and dictionaries; Encyclopedias and dictionaries; MCE